Thematization Analysis on Basuki Tjahaya Purnama Staement on Surah al-Ma’ida 51 - Syaepul Uyun, Aip (Universitas PGRI Adi Buana Surabaya, 2021)
This paper aims to give a description on depth understanding of Surah Al-Ma’ida 51 and Ahok’s statement analysis related to Surah Al-Ma’ida 51 which is believed that it had insulted Muslim community. The writer used thematisation context to analyze the data. It is done to find out the starting point of Ahok’s utterances as the main key words of the base of the rest sentences. This theme can be inferred as an intention or motivation and also the purpose of the utterances. The writer analyzed the script of the video provided by the Jakarta Post published on Monday 10 Oktober 2016. Hence, after analyzing the syntactical form and also the theme of the utterances, it can be inferred that this statement does not consist any intention of insulting particular religion (Islam). It can be seen from the sentence starting point which is the residents of Thousand Islands and not Surat Al-Ma’ida.